5(x+2)-1=3x+2(3+x)

Simple and best practice solution for 5(x+2)-1=3x+2(3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)-1=3x+2(3+x) equation:


Simplifying
5(x + 2) + -1 = 3x + 2(3 + x)

Reorder the terms:
5(2 + x) + -1 = 3x + 2(3 + x)
(2 * 5 + x * 5) + -1 = 3x + 2(3 + x)
(10 + 5x) + -1 = 3x + 2(3 + x)

Reorder the terms:
10 + -1 + 5x = 3x + 2(3 + x)

Combine like terms: 10 + -1 = 9
9 + 5x = 3x + 2(3 + x)
9 + 5x = 3x + (3 * 2 + x * 2)
9 + 5x = 3x + (6 + 2x)

Reorder the terms:
9 + 5x = 6 + 3x + 2x

Combine like terms: 3x + 2x = 5x
9 + 5x = 6 + 5x

Add '-5x' to each side of the equation.
9 + 5x + -5x = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + 0 = 6 + 5x + -5x
9 = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 = 6 + 0
9 = 6

Solving
9 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x^2+y^2=4225 | | -6(3x-4)+1=-18+25 | | 3T^2-3T+4= | | 6y+4=5y-6 | | (5y^4+2x^3y)dx=(4xy^3+x^4)dy | | 5x^2-23=0 | | =2T^2+3T-4 | | 4(3x-2)-3=4(x-3)+57 | | 2T^2+3T-4= | | k^2-k-7=0 | | 7z=13-48 | | 2(2x-3)-2=2(x-3)+14 | | 3(x+6)+4(2x-5)= | | x=0.8571428571+1.142857143y | | X=2.25+.25 | | 2m+27=-7-2m | | 5h+15-3h=31 | | x(x+10)=240 | | 2w^2+8w-192=0 | | w^2+.13w-.051=0 | | 4x+98=134 | | x+3(3x+6)=27x+99 | | 25x^2+20x+60=100 | | x^2+10x+y^2-6y=50 | | (6u^3v)(-5u^7v^6)= | | -3.92=7.2-11.6x | | 4x-4x=5b+3x | | 2x+5(3-x)=1+4x | | -c^2+4c+4=-2c^2 | | 5b^2+28b+19=4 | | 4sin^2(3x)-3=0 | | N+16=m |

Equations solver categories